Catalyst-Free Tandem Ring-Opening/Click Reaction of Acetylene-Bearing Donor–Acceptor Cyclopropanes - Flisar, Michelle E.; Emmett, Michael R.; Kerr, Michael A. (Synlett, 2014)
Cyclopropane-1,1-hemimalonates bearing a 2-(2-alkynylphenyl) moiety underwent ring opening by an azide nucleophile, generating an alkyl azide that, in turn, underwent [3+2]-dipolar cycloaddition with the alkyne. The products are novel linearly fused tricyclic 1,2,3-triazoles.
Keywords: heterocycles; cycloaddition; cyclopropanes; triazole; click chemistry